Sustainable Marketing: Integrating Environmental Aspects in Corporate Marketing Plans - Dewi Indriani Jusuf (Jurnal Info Sains : Informatika dan Sains, 2022)
This research aims to analyze the effectiveness of integrating environmental aspects in company marketing plans as part of efforts to achieve sustainable marketing. Using a theoretical framework involving the concepts of sustainable marketing and corporate social responsibility, this research analyzes the impact of integrating environmental aspects on brand image, consumer loyalty and company financial performance. This research uses a qualitative approach with descriptive methods. This research emphasizes the importance of sustainable marketing practices for companies amidst pressure to be socially and environmentally responsible. The integration of environmental, social and corporate governance factors into marketing strategies allows companies to reduce negative impacts on the environment and build strong relationships with consumers who care about social and environmental issues. Key steps include efficient use of resources, support of sustainable suppliers, development of environmentally friendly products, and education of consumers about the company's sustainability efforts. Consistency in messaging and commitment to sustainability can also strengthen brand image and employee engagement, thereby playing an important role in advancing global sustainability and societal well-being.